Micropropagation of Cymbidium aloifolium (L.) SW., A Medicinal Orchid by Artificial Seeds Technology - Pradhan, Shreeti; Tiruwa, Babu Lal; Subedee, Bijay R; Pant, Bijaya (Journal of Natural History Museum, 2015)
Artificial seed technology is a rapidly growing area of research in plant cell and tissue culture. Application of this technology opens an alternative route for mass scale production, efficient delivery of cloned plantlets and fulfils the increasing demand of local growers. An attempt was made to produce artificial seeds and their subsequent regeneration of a highly valuable medicinal orchid of Nepal i.e. Cymbidium aloifolium. Artificial seeds were obtained through encapsulation of protocorms in calcium alginate beads. Protocorms were encapsulated by using 3% sodium alginate and 0.2 M calcium chloride solution. Murashige and Skoog (MS) medium (1962) was used as the basal medium for in vitro germination and seedling development of artificial seed. In Cymbidium aloifolium, 20-25 days old in vitro grown protocorms were used for production of artificial seeds. Artificial seeds were inoculated on two different culture conditions of MS medium i.e. MS solid & MS liquid with four different treatments i.e. strength of 1.0, ½, ¼ and MS media supplemented with plant growth regulators viz. BAP (0.5 mg/l) and NAA (0.5 mg/l). Highest percentage of germination (100%) and plantlet conversion was found on hormone free full strength (1.0 MS) of MS liquid medium after 13-14 weeks of culture. Plantlets regenerated from artificial seeds with well developed shoot and root systems were successfully acclimatized in potting mixture of cocopeat, litter and sphagnum moss in a ratio 2:1:1.J. Nat. Hist. Mus. Vol. 28, 2014: 42-48